CONSTRUCTION OF CONCRETE BEAMS WITH COMPOSITE REINFORCEMENT - Umarov Shodiljon Abdug ‘ofurovich; Abobakirova Zebuniso Asrorovna (Journals Park Publishing, 2023)
This article presents an analysis of the results of research work on the study of composite reinforcement elements, widely used at present in the restoration of concrete structures in buildings and structures under construction in the Republic of Uzbekistan and abroad.
Keywords: composite, basalt, concrete, smoothness, strength, texture, polymer.